Evaluation Study Of Walkability Index In Central Business District (CBD) Area, Pekanbaru City - Muhammad Sofwan; Mira Hafizhah Tanjung (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
Walkable cities emphasize cities with high walkability values, where walkability can be defined as the degree to which the environment can be pedestrian friendly. Walkable city is considered to be able to increase people's desire to walk so that it can make the environment more humanistic and can also help realize one of the objectives of sustainable transportation. The value of walkability can be viewed from the perspective of the urban form (macro level) of an area. The Central Business District (CBD) Pekanbaru City walkability index assessment uses the WAI IPEN Project model that measures the form of the Urban Form. The walkability assessment process in the Pekanbaru Kota Sub-District Area (CBD) divides the study area into 6 grids. The analysis shows that there are 4 grids that have a negative walkability value. In the analysis of the walkability value pattern it can be seen that the area dominated by office activities has a lower walkability value compared to the area that has mixed land use.